2010
DOI: 10.3103/s0096392510040243
|View full text |Cite
|
Sign up to set email alerts
|

Population-genetic analysis of Deschampsia antarctica from two regions of maritime antarctica

Abstract: Сравнительный анализ последовательностей участка ITS1-2 рДНК D. antarctica показал, что после ледникового периода в Антарктику могли мигрировать растения вида с различ-ными генотипами. Применение RAPD-маркеров обнаружило различия в уровне полимор-физма между популяциями D. antarctica, расположенными в разных широтах, а также огра-ниченность обмена генетическим материалом между ними.Ключевые слова: Deschampsia antarctica, RAPD-анализ, ITS рДНК, Антарктика. Deschampsia antarctica Desv. является одним из двух … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…2) in Antarctica (which is also present in central and southern Patagonia) and the higher migration rates from Patagonia to Antarctica (Table 3) support the hypothesis of dispersal from a South American origin to Antarctica, as hinted at by Van de Wouw et al (2008). The single Antarctic ITS haplotype is also in agreement with previous studies depicting a low genetic diversity in Antarctic populations (Holderegger et al, 2003;Andreev et al, 2010;Volkov et al, 2010). The lower number of haplotypes for both markers (one nuclear and four plastid) found in Antarctica supports the formation of the gene pool from a small number of initial genotypes (i.e.…”
Section: Discussion Genetic Variation In the Antarctic Hair Grasssupporting
confidence: 91%
See 1 more Smart Citation
“…2) in Antarctica (which is also present in central and southern Patagonia) and the higher migration rates from Patagonia to Antarctica (Table 3) support the hypothesis of dispersal from a South American origin to Antarctica, as hinted at by Van de Wouw et al (2008). The single Antarctic ITS haplotype is also in agreement with previous studies depicting a low genetic diversity in Antarctic populations (Holderegger et al, 2003;Andreev et al, 2010;Volkov et al, 2010). The lower number of haplotypes for both markers (one nuclear and four plastid) found in Antarctica supports the formation of the gene pool from a small number of initial genotypes (i.e.…”
Section: Discussion Genetic Variation In the Antarctic Hair Grasssupporting
confidence: 91%
“…Population genetic studies conducted so far on D. antarctica have been restricted to the Antarctic and sub-Antarctic islands, revealing overall a low genetic diversity and a discrete genetic diversity gradient from a maximum value in the Falkland Islands to a minimum in the Antarctic Peninsula (Holderegger et al, 2003;Chwedorzewska, Bednarek & Puchalski, 2004;Chwedorzewska, 2006;Chwedorzewska & Bednarek, 2008;Van de Wouw, Van Dijk & Huiskes, 2008). Other studies including sequences from Tierra del Fuego (Andreev et al, 2010: one sequence;Volkov et al, 2010: two sequences) were inconclusive about the genetic structure and history of the species.…”
Section: Introductionmentioning
confidence: 99%
“…Considering all chromosomal aspects of the studied populations of D. antarctica, the South American populations are more variable than the Antarctic. Molecular studies conducted using AFLP, RAPD, sequences of the chloroplast and nuclear ITS (Holderegger et al 2003;Chwedorzewska et al 2008;Van de Wouw et al 2008;Andreev et al 2010;Volkov et al 2010) suggest that Antarctic populations generally have low genetic variation and that diversity increases at lower latitude (Holderegger et al 2003;Van de Wouw et al 2008). Until now, no genetic studies have included Patagonian and Antarctic populations; however, preliminary results from ITS sequences suggest that Patagonian populations of D. antarctica have more genetic variability that Antarctic populations (Fasanella et al in preparation).…”
Section: Origin and Chromosomal Diversification In D Antarcticamentioning
confidence: 99%
“…But there is another task, to follow how the longterm conditions in different regions have influenced their accumulated in nature adaptive capacity to pre servation. This is more interesting because genetic studies of this species have shown a fairly low genetic heterogeneity (Andreev et al, 2010;Navrotska et al, 2017). The results of our previous studies of individual D. antarctica plants' adaptability of different origins are presented in (Miryuta et al, 2016;Parnikoza et al, 2017).…”
Section: Introductionmentioning
confidence: 96%